PENGARUH KUALITAS PRODUK (PRODUCT QUALITY) DAN KUALITAS LAYANAN (SERVICE QUALITY) TERHADAP KEPUASAN KONSUMEN (CONSUMER SATISFACTION) (Studi pada Konsumen E-Commerce B2C Zalora.co.id di Kota Semarang) - Paku Islamiati; Agus Hermani DS (Universitas Diponegoro, 2019)
The reseacrh runs from high issues of e-commerce consumer complaints in Indonesia. The aims of this research are to know the effect of product quality and service quality on consumer satisfaction at e-commerce B2C Zalora.co.id. The sample of this research is 100 respondents that ever have done a minimum transaction one time in ecommerce Zalora.co.id, 17 years old for a minimum, and domiciled in Semarang city both temporarily or permanently. This research consists of 3 variables, 12 indicators, and 3 hypotheses. Instrument analysist is used SPSS 16.0 for Windows to analyze the data, by doing validity test, reliability test, a coefficient of correlation, a coefficient of determination, simple and multiple linear regression, and test of significance (t-test and F test). The result of this research for partially is showing that product quality has a positive and significant effect to customer satisfaction with result Y = -3,198 + 1,088X1, service quality also has a positive and significant effect to customer satisfaction with result Y = -5,238 + 1,332X2. Product quality and service quality simultaneous has an effect to customer satisfaction with result Y = -6,002 + 0,809X1 + 0,500X2. Coefficient determination of X1 is 73,1% and X2 is 59,5%. According to that result, the researcher has some recommendations are for Zalora.co.id to increasing their product quality especially for material suitability, durability, and model variations. And also to improve their service quality especially for the delivery time, refund process, and return process. Because from the variable indicator based on the value chart of the avarage, all three indicators were badly assessed by the respondents.